Kajian Literatur tentang Konsep, Sifat, dan Aplikasi Fungsi Kuadrat dalam Pembelajaran Matematika Menengah - Angelica Sigalingging; Nurhasanah Siregar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is a literature review aimed at examining in depth the concepts, characteristics, learning difficulties, and applications of quadratic functions in secondary mathematics education. The research employs a qualitative approach by analyzing ten articles published between 2019 and 2025 from both national and international journals. The findings indicate that the quadratic function is a fundamental topic in the mathematics curriculum, playing a crucial role in developing higher-order mathematical thinking skills such as analysis, synthesis, and problem-solving. It also serves as a foundation for understanding more advanced topics such as calculus, analytic geometry, and optimization. However, various studies have found that students continue to face significant learning difficulties, including misconceptions related to the shape of the parabola graph, understanding the discriminant value, and connecting algebraic forms to real-world contexts. To address these issues, research suggests that technology-assisted learning—particularly through interactive software such as GeoGebra—has proven effective in enhancing conceptual understanding, motivation, and student engagement. Therefore, this review highlights the importance of strengthening conceptual understanding, applying contextual learning approaches, and integrating digital technology as innovative strategies for teaching quadratic functions at the secondary education level.